Morphological variability in fruits from a single tacaco [Sechium tacaco (Pittier) C. Jeffrey] population along the time - Monge-Pérez, José Eladio (2018)
The morphological characteristics of fruits from a single tacaco population from Costa Rica were measured in June 2013 and September 2015. Ten quantitative variables were compared. There were statistically significant differences between evaluation dates for the following fruit variables: weight, width, thickness, number of complete longitudinal sutures, number of incomplete longitudinal sutures, length/width ratio, and length/thickness ratio. There were no significant differences for fruit length, number of fruit spines, and fruit width/thickness ratio. This is the first notice about the morphological variability in tacaco fruits of a single population along the time. These results provide evidence of the gene flow magnitude in this species.